Effects of nitrogen gas fumigation on postharvest quality of minimally processed starfruit (Averrhoa carambola L.) stored at low temperature - Wan Zaliha Wan Sembok,; Koh, Suet Yen (Penerbit Universiti Kebangsaan Malaysia, 2017)
Minimally processed (MP) fruit have a short post-cutting life due to the mechanical injury during processing which increase the browning incidence, tissue softening, as well as the nutrient loss and flavor. The browning incidence occurs due to the destructive of cellular compartmentation which allow the phenolic substrate to be assessable to Polyphenol Oxidase (PPO) that catalyze phenolic oxidation. Therefore, the appearance, organoleptical properties and nutritional quality are reduced in MP starfruit. In this study, the effect of six different volumes of nitrogen gas (N2) (0 mL, 5 mL, 10 mL, 15 mL, 20 mL and 25 mL) fumigation on postharvest quality of MP starfruit (Averrhoa carambola L.) stored at 5°C were investigated. Flesh colour, browning index, total phenolic content, soluble solids concentration (SSC), titratable acidity (TA), firmness and ascorbic acid concentration of MP starfruit were determined for 12 days period. No significant differences of various N2 fumigation treatments were recorded in all postharvest parameters except for percentage weight loss. However, N2 fumigation at higher volume, 25 mL was a promising value to reduce browning index as well as maintain MP fresh colour and total phenolic content. In conclusion, the application of 25ml N2 gas has a tendency to be the best volume in reducing browning incidence and maintaining other quality attributes of MP starfruit.